A sedução eficaz: o papel das glândulas extraflorais na atração de aranhas como protetoras biológicas - Dias, Karoline Pádua de Oliveira (2023)
Spiders are diverse and represent important predators in all terrestrial ecosystems, however, only a few studies have examined their role in spider-plant interactions. In the present study, we tested the hypothesis that spiders can act by reducing the abundance of herbivores in vegetation, and that when these organisms are in association with plants, this would result in a lower loss of leaf area and increased fitness (production of flowers, fruits and seeds) for the producer, this relationship being more intense when the plant provides an additional resource, such as extrafloral nectar. Our study was conducted in a Savanna protected area, in cerrado sensu stricto vegetation, using the species Heteropoterys pteropetala A. Juss. (Malpighiaceae), a shrub with extrafloral nectaries,. We recorded phenological information of H. pteropetala during one year, as well as made records of insects and spiders present, in two groups of plants: a control group, in which the nectaries were active, and a treatment group, in which the nectaries were manipulated, becoming inactive. The results indicated that spiders had different effects on plants with and without active nectaries. They reduced leaf area loss in plants that provided the extrafloral nectar resource, but did not alter bud, fruit and seed production, confirming our hypothesis of protection against herbivores, but refuting our hypothesis of increased fitness. Benefits to plants were greatest during the reproductive period, coinciding with the peak of spider’s abundance. Our results indicate that protection against herbivory by spiders in the tropical savanna is related to the plant's energy expenditure on extrafloral nectar production and its reproductive period, since structures such as buds and flowers attract possible prey for spiders and they also use the nutritional resource, nectar.